2001
DOI: 10.1007/s002770100294
|View full text |Cite
|
Sign up to set email alerts
|

Histological subtypes of Hodgkin's disease in the setting of HIV infection

Abstract: The relative incidence of Hodgkin's disease (HD) has been found to have increased approximately seven times in HIV-infected patients. We analyzed the histological distribution of HIV-associated HD with the aim of clarifying purported difference(s) from de novo HD. References on HIV/AIDS-associated HD were retrieved from the most complete databases. Nineteen articles were the subject of our analysis. Seventeen of them reported data on the histological type of HIV/AIDS-associated HD patients; the route of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 35 publications
2
1
0
Order By: Relevance
“…Whereas MCCHL and LDCHL were strongly associated with HIV infection, all NSCHL, the most commonly diagnosed HL type in Rwanda, were HIV negative. This is consistent with studies in high‐income settings,21, 22, 23 but is the first formal report from sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Whereas MCCHL and LDCHL were strongly associated with HIV infection, all NSCHL, the most commonly diagnosed HL type in Rwanda, were HIV negative. This is consistent with studies in high‐income settings,21, 22, 23 but is the first formal report from sub‐Saharan Africa.…”
Section: Discussionsupporting
confidence: 91%
“…Similar proportions of death due to HIV were observed in these subgroups. These results are consistent with many prior studies that have shown mixed cellularity and lymphocyte-depleted HL to be more common among HIV-infected individuals, and have shown the risk of these subtypes is particularly high (5, 9, 23, 24). These subtypes are also known to have the strongest association with EBV (25).…”
Section: Discussionsupporting
confidence: 92%
“…Coinfection with EBV occurs in 90–100% of cases, compared to 30–40% in HIV-negative patients) [ 172 ]. In HIV-related cHL, mixed cellularity is the most common subtype, followed by lymphocyte depletion and nodular sclerosis [ 29 , 35 , 173 ].…”
Section: Implications Of Epstein–barr Virus In the Different Hiv-related Lymphoma Typesmentioning
confidence: 99%